Quality of life before admission to the intensive care unit - Tereran, Nathalia Perazzo (Associação Brasileira de Medicina intensiva, 2012)
OBJECTIVE: To examine the reliability of the SF-36 general health questionnaire when used to evaluate the health status of critically ill patients before admission to intensive care and to measure their health-related quality of life prior to admission and its relation to severity of illness and length of stay in the intensive care unit. METHODS: Prospective cohort study conducted in the intensive care unit of a public teaching hospital. Over three months, communicative and oriented patients were interviewed within the first 72 hours of intensive care unit admission; 91 individuals participated. The APACHE II score was used to assess severity of illness, and the SF-36 questionnaire was used to measure health-related quality of life. RESULTS: The reliability of SF-36 was verified in all dimensions using Cronbach's alpha coefficient. In six dimensions of eight domains the value exceeded 0.70. The average SF-36 scores of the health-related quality of life dimensions for the patients before admission to intensive care unit were 57.8 for physical functioning, 32.4 for role-physical, 53.0 for bodily pain, 63.2 for general health, 50.6 for vitality, 56.2 for social functioning, 54.6 for role-emotional and 60.3 for mental health. The correlations between severity of illness and length of stay and the health-related quality of life scores were very low, ranging from -0.152 to 0.175 and -0.158 to 0.152, respectively, which were not statistically significant. CONCLUSION: In the sample studied, the SF-36 demonstrated good reliability when used to measure health-related quality of life in critically ill patients before admission to the intensive care unit. The worst score was role-physical and the best was general health. Health-related quality of life of patients before admission was not correlated with severity of illness or length of stay in the intensive care unit.